pengaruh e-service quality e-trust dan e-wom terhadap customer satisfaction pada pengguna e-commerce shopee di kecamatan ubud - Dita Segarini, Ni Kadek; Meryawan, I Wayan; Fitriandari, Mahayanti (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2025)
E-commerce is very popular nowadays, thereby intensifying competition between e-commerce. Customer satisfaction or customer satisfaction in e-commerce is the main goal in retaining customers. Customer satisfaction or customer satisfaction in e-commerce can be influenced by several factors, including e-service quality, e-trust and E-WOM. The achievement of this research is to determine the simultaneous and partial influence between e-service quality, e-trust and E-WOM on customer satisfaction among Shopee e-commerce users in Ubud sub-district, the number of which cannot be identified with certainty, the research sample This consisted of 100 respondents using accidental sampling. Data hypothesis testing in this research uses multiple linear regression, determination analysis, statistical analysis of the F test (F-test) and statistical analysis of the t test (t-test). Based on the research results, it can be seen that e-service quality has a partially positive and significant effect on customer satisfaction, e-trust has a partially positive and significant effect on customer satisfaction, E-WOM has a partially positive and significant effect on customer satisfaction, and e-service quality, e-trust and E-WOM are simultaneously significant to customer satisfaction. E-service quality, e-trust and E-WOM have a strong impact on customer satisfaction when using applications, especially the Shopee e-commerce application